Analysing the nexus between financial structure and monetary policy impulses in sub-Saharan Africa - Raad M. Al-Tal; Jephias Makiwa (South African Journal of Economic and Management Sciences, 2024)
Background: Gains in improving bank efficiency have widely been regarded as one of the most effective means of ensuring sustainability in a financial system.